Marvin Redpost : Kidnapped at birth - Sachar, Louis, 1954-; Hellard, Susan (London : Bloomsbury, 2010)
Marvin lives in a grey house with a white fence - a white fence but for one red post. He has red hair and blue eyes. He is left-handed. 'We're lucky to be left-handed', said Mrs North, 'It means we have royal blood'. One day, at school, Marvin realises his parents have brown hair and they have brown eyes. Can he really be Marvin Redpost?
Originally published: 2004.
3-6.
Keywords: Redpost, Marvin -- (Fictitious character); Kidnapping -- Fiction; Children's stories